Distribution of CR1-like transposable element in woodpeckers (Aves Piciformes): Z sex chromosomes can act as a refuge for transposable elements - Bertocchi, Natasha Avila; de Oliveira, Thays Duarte; del Valle Garnero, Analía; Coan, Rafael Luiz Buogo [UNESP]; Gunski, Ricardo José; Martins, Cesar [UNESP]; Torres, Fabiano Pimentel (Springer Nature, 2018)
Birds have relatively few repetitive sequences compared to other groups of vertebrates; however, the members of order Piciformes (woodpeckers) have more of these sequences, composed mainly of transposable elements (TE). The TE most often found in birds is a retrotransposon chicken repeat 1 (CR1). Piciformes lineages were subjected to an expansion of the CR1 elements, carrying a larger fraction of transposable elements. This study compared patterns of chromosome distribution among five bird species, through chromosome mapping of the CR1 sequence and reconstructed their phylogenetic tree. We analyzed several members of Piciformes (Colaptes campestris, Colaptes melanochloros, Melanerpes candidus, and Veniliornis spilogaster), as well as Galliformes (Gallus gallus). Gallus gallus is the species with which most genomic and hence cytogenetic studies have been performed. The results showed that CR1 sequences are a monophyletic group and do not depend on their hosts. All species analyzed showed a hybridization signal by fluorescence in situ hybridization (FISH). In all species, the chromosomal distribution of CR1 was not restricted to heterochromatin regions in the macrochromosomes, principally pair 1 and the Z sex chromosome. Accumulation in the Z sex chromosomes can serve as a refuge for transposable elements. These results highlight the importance of transposable elements in host genomes and karyotype evolution.
Keywords: Birds; FISH; Genome organization; Genomes; Retrotransposon; Sex chromosomes